The role of serial lactate and liver enzyme dynamics in predicting post hepatectomy liver failure - Soldati, Vuyolwethu Sonwabile (Division of General Surgery, 2023)
Background: Post-hepatectomy liver failure (PHLF) is an important cause of morbidity and mortality following liver resection. Current prognostic models only allow for the detection of PHLF on post-operative day 5. Earlier detection and intervention may improve outcomes. To date, no studies have evaluated serial post-operative lactate and liver function tests (LFT) to predict PHLF. Aim: This study evaluated the prognostic utility of serial lactate concentrations and LFTs to predict PHLF following hepatectomy. Methods: All major liver resections (≥ 3 Couinaud segments) undertaken at Groote Schuur Hospital and UCT Private Academic Hospital from May 2018 to April 2021 were included. Lactate levels were measured 4-hourly for the first 24 hours post hepatectomy and daily LFTs for the first 5 days. Associations between baseline patient characteristics and lactate dynamics in PHLF as well as the predictive value of lactate, INR and bilirubin were determined. Results: Forty-seven patients, mean age 56.5 (±13.2) years, of whom 24 were males were assessed. Five (10.6%) patients had PHLF and were older (67.4 ± 12.2) and were predominantly men (80%)...